The exploration of the relationships between the global competitiveness, the ICT and education - Yildiz, Turkay (Business, Management and Economics Engineering, 2016)
Information and Communication Technology (ICT) is a key element for development and economic expansion. However, many of the developing countries appear to gain only small fraction of the advantages from the ICT sectors. Indeed, developed countries are taking the most of the advantages and opportunities brought by the use of ICT. Therefore, it is necessary to highlight the essential role and the significant relationship of ICT and education for gaining the competitive advantage. In this regard, this study investigates the complex relationships of some of the global competitiveness indicators of the ICT, education and the business sophistication and innovation factors. In this study, several statistically significant relationships are explored by applying canonical correlation analysis. These findings and significant statistical results are highlighted.